Dolor cervical como presentación de neumomediastino espontáneo en urgencia pediátrica. Caso clínico - Guzmán N., Miguel; Osses M., Gabriela (Revista Hospital Clínico Universidad de Chile, 2016)
Spontaneous Pneumomediastinum is a rare clinical situation in pediatric emergency services, sometimes it presents with guiding symptoms, but in other occasions in a very nonspecific way. Definitely, needs to be highly suspected, emphasizing in the anamnesis the antecedent of intense physical exercise before the development of the triggering symptoms that determinates the consult, generally having a good evolution that gets solved in 3-4 days. There is a pediatric clinical case presented, that permits us to discuss the more relevant aspects of the clinical presentation, diagnosis methods and the updated management, in pediatric emergency services.